Circular RNA hsa_circ_0004277 Stimulates Malignant Phenotype of Hepatocellular Carcinoma and Epithelial-Mesenchymal Transition of Peripheral Cells - Zhu, Chuanrong; Su, Yang; Liu, Lei; Wang, Shaochuang; Liu, Yuting; Wu, Jinsheng (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence shows that exosomal circRNAs reflect the physiological status of donor cells, and various cell reactions are induced after exosomal circRNAs are captured by recipient cells. In this study, qRT-PCR was performed to detect circ-0004277 expression in hepatocellular carcinoma (HCC) cell lines, tissues, and plasma exosomes. The effects of circ-0004277 on the proliferation and migration of HCC cells were assessed by cell counting, 5-ethynyl-2'-deoxyuridine assays, Transwell migration assays, and tumor formation in nude mice. We found that circ-0004277 was significantly upregulated in HCC cells, tissues, and plasma exosomes compared to that in normal controls. Overexpression of circ-0004277 enhanced the proliferation, migration, and epithelial-mesenchymal transition (EMT) of HCC cells in vivo and in vitro. Furthermore, exosomes from HCC cells enhanced circ-0004277 expression in surrounding normal cells and stimulated EMT progression. ZO-1, a tight junction adapter protein, was downregulated in HCC tissues. In conclusion, our findings suggest that circ-0004277 promotes the malignant phenotype of HCC cells via inhibition of ZO-1 and promotion of EMT progression. In addition, exosomal circ-0004277 from HCC cells stimulates EMT of peripheral cells through cellular communication to further promote the invasion of HCC into normal surrounding tissues.